High-resolution 3D imaging uncovers organ-specific vascular control of tissue aging - Chen, Junyu; Sivan, Unnikrishnan; Tan, Sin Lih; Lippo, Luciana; Angelis, Jessica De; Labella, Rossella; Singh, Amit; Chatzis, Alexandros; Cheuk, Stanley; Medhghalchi, Mino; Gil, Jesus; Hollander, Georg; et al. (Science advances, 2021)
Blood vessels provide supportive microenvironments for maintaining tissue functions. Age-associated vascular changes and their relation to tissue aging and pathology are poorly understood. Here, we perform 3D imaging of young and aging vascular beds. Multiple organs in mice and humans demonstrate an age-dependent decline in vessel density and pericyte numbers, while highly remodeling tissues such as skin preserve the vasculature. Vascular attrition precedes the appearance of cellular hallmarks of aging such as senescence. Endothelial VEGFR2 loss-of-function mice demonstrate that vascular perturbations are sufficient to stimulate cellular changes coupled with aging. Age-associated tissue-specific molecular changes in the endothelium drive vascular loss and dictate pericyte to fibroblast differentiation. Lineage tracing of perivascular cells with inducible PDGFRβ and NG2 Cre mouse lines demonstrated that increased pericyte to fibroblast differentiation distinguishes injury-induced organ fibrosis and zymosan-induced arthritis. To spur further discoveries, we provide a freely available resource with 3D vascular and tissue maps. - 3D tissue imaging reveals maladaptations of blood vessels in organ aging, fibrosis, and arthritis. - 3D tissue imaging reveals maladaptations of blood vessels in organ aging, fibrosis, and arthritis.
Gesehen am 06.04.2021